2017
DOI: 10.1038/s41550-017-0147
|View full text |Cite
|
Sign up to set email alerts
|

A universal minimal mass scale for present-day central black holes

Abstract: Intermediate-mass black holes (IMBHs) of mass M • ≈ 10 2 -10 5 solar masses, M , are the long-sought missing link 1 between stellar black holes, born of supernovae 2 , and massive black holes 3 , tied to galaxy evolution by the empirical M • /σ correlation 4,5 . We show that low-mass black hole seeds that accrete stars from locally dense environments in galaxies following a universal M • /σ relation 6, 7 grow over the age of the Universe to be above M 0 ≈ 3 × 10 5 M (5% lower limit), independent of the unknown… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…A potential limitation of our model is the assumed evolution of the TDE rate with redshift following the IMBH number density. Recent studies suggest that black holes of intermediate and small mass might be less numerous today than in the past because they may have merged into more massive black holes 65 . This would suggest a less negative, or even positive evolution of the TDE rate with redshift for which the combined description of UHECR and PeV neutrino data rapidly becomes more challenging (see also the Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…A potential limitation of our model is the assumed evolution of the TDE rate with redshift following the IMBH number density. Recent studies suggest that black holes of intermediate and small mass might be less numerous today than in the past because they may have merged into more massive black holes 65 . This would suggest a less negative, or even positive evolution of the TDE rate with redshift for which the combined description of UHECR and PeV neutrino data rapidly becomes more challenging (see also the Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…We carried out direct N-body simulations of the merger of three stellar clusters to form an NSC to investigate the outcome of simulated runs containing zero, one, two and three IMBHs. If a single IMBH is delivered to the galactic nuclei, it can be retained there and can subsequently grow from gas accretion (Das et al 2021a;Natarajan 2021) or tidal capture and disruption of stars (Stone et al 2017;Alexander & Bar-Or 2017;Boekholt et al 2018;Dittmann & Miller 2020). If multiple IMBHs are delivered to the NSC, then we found that an IMBH binary is likely to form and merge due to gravitational wave (GW) radiation.…”
Section: Introductionmentioning
confidence: 85%
“…As discussed in Askar et al (2021), several studies have hypothesized that IMBHs of 10 2 − 10 4 M can form in dense stellar clusters (see Greene et al 2020, and references therein), either through runaway mergers of massive stars that may lead to the formation of a seed IMBH (Portegies Zwart & McMillan 2002;Gürkan et al 2004;Freitag et al 2006;Giersz et al 2015;Mapelli 2016;Gieles et al 2018;Reinoso et al 2018;Tagawa et al 2020;Alister Seguel et al 2020;Das et al 2021b), or through the gradual growth of stellarmass BHs and their progenitors via mergers with other BHs or stars (Miller & Hamilton 2002;Giersz et al 2015;Rizzuto et al 2021;González et al 2021;Di Carlo et al 2021). BHs of 10 2 − 10 3 M may grow to larger masses through tidal capture and disruption events in dense clusters (Stone et al 2017;Alexander & Bar-Or 2017;Sakurai et al 2019). Moreover, stellar-mass seed BHs can also grow by accretion of gas in primordial, gas-rich, massive stellar clusters (Vesperini et al 2010;Leigh et al 2013).…”
Section: Populating Galactic Nuclei With Imbhsmentioning
confidence: 99%
“…However, independent studies performed at the same time indicated opposite results: simulations show that the stellar debris from tidal disruption events could fuel and grow seed black holes (Alexander & Bar-Or 2017;Zubovas 2019;Pfister et al 2020) whose feedback could become relevant and have significant effects on the host galaxy (Zubovas 2019). Observationally, long-slit and integral-field spectroscopy studies of two different samples of quiescent dwarf galaxies revealed that they possibly host AGN, which could be preventing the formation of stars in such galaxies (Dickey et al 2019;Penny et al 2018).…”
Section: Agn Vs Sn Feedback In Dwarf Galaxiesmentioning
confidence: 99%